Comparative Analysis of Chitin SynthaseA dsRNA Mediated RNA Interference for Management of Crop Pests of Different Families of Lepidoptera - Rana, Seema; Rajurkar, Ashish B.; Kumar, K. K.; Mohankumar, Subbarayalu (Frontiers in Plant Science, 2020)
RNA interference (RNAi) is a sequence-specific down-regulation in the expression of a particular gene, induced by double-stranded RNA (dsRNA). Feeding of dsRNA either directly or through transgenic plants expressing dsRNA of insect genes has been proven successful against lepidopteran and coleopteran pests, establishing an additional alternative to control insect pests. Lepidopteran crop pests including Spodoptera litura (Fabricius) (Noctuidae), Chilo partellus (Swinhoe) (Crambidae), Plutella xylostella (Linnaeus) (Plutellidae) and Maruca vitrata (Fabricius) (Pyralidae) are the devastating pests of a variety of crops. To tap the potential of RNAi against insect pests, a gene coding for the key enzyme in chitin biosynthesis in arthropods, the chitin synthaseA (CHSA), has been targeted through an exogenous delivery of dsRNA and plant-mediated RNAi. The introduction of dsCHSA caused “Half ecdysis” and “Black body” type lethal phenotypes and a significant reduction in larval body weight. Subsequent RT-qPCR analysis demonstrated the down-regulation of CHSA gene transcripts from 1.38 to 8.33 fold in the four target species. Meanwhile, when S. litura larvae fed with leaves of transgenic tobacco plants expressing dsSlCHSA, the mRNA abundance of CHSA gene was significantly decreased resulting in lethal phenotypes like “Double head formation”, “Half ecdysis”, and “Black body”. In addition, abnormalities in pupal-adult and adult stage were also documented, strongly suggesting the RNAi effect of CHSA gene at late developmental stages. Overall, the results demonstrated that CHSA gene expression in Lepidopteran crop pests could be suppressed by application of dsRNA either as feeding or through transgenic crop plants.